An Identity-Based Authentication Scheme in Cloud Computing - Zhi-Hua Zhang; Jiang Xue-Feng; Jian-Jun Li; Wei Jiang (2012 International Conference on Industrial Control and Electronics Engineering, 2012)
Cloud computing is a hot topic of current research, and identity-based authentication is important in many applications scenarios of e-business based on cloud computing, in these e-business scenarios users should prove the user's legacy, and the enterprise needs to determine whether the user has the right popedom, so this paper presents a identity-based authentication scheme for this applications, and this scheme avoids the issues how to revocation public key certificate and the escrow problem of key, and then the security of the scheme is analyzed, at last the communication process of the identity-based authentication scheme is described.